Numerical taxonomy of Abelmoschus Medik. (Malvaceae) in India (Bangladesh Journal of Plant Taxonomy, 2015)
In the present study, numerical taxonomy approach has been used for the first time to access the taxonomy and species relationships of Abelmoschus. Sixteen Abelmoschus taxa were subjected to cluster analysis using 52 diagnostic characters related to root, stem, leaf, flower, fruit and seed. In this analysis, the first six principal components (PCs) accounted for the total variance of 79.22%. Similarity values for all 17 operational taxonomic units (OTUs) ranged from 0.18 to 0.82 with an average of 0.34. Abelmoschus sagittifolius showed maximum similarity value of 0.82 with A. moschatus subsp. tuberosus. On the other hand, minimum similarity values (0.18) were observed between A. tuberculatus and A. moschatus subsp. tuberosus, A. tuberculatus and A. sagittifolius, A. palianus and A. moschatus subsp. tuberosus, and A. palianus and A. sagittifolius. Neighbour joining (NJ) cluster analysis clearly discriminated 17 OTUs into four major clusters. The present study also validates the utility of morphometric analysis of Abelmoschus with respect to the taxonomy and species relationships.Bangladesh J. Plant Taxon. 22(2): 87-98, 2015 (December)